In Vitro Characterization of Indigenous Coconut Varieties (Cocos nucifera L.) of Sri Lanka for Water Stress Tolerance - Fernando, S. C.; Santha, E. S.; Perera, S. A. C. N.; Dissanayake, H. D. M. A. C.; Meegahakumbura, M. G. M. K.; Perera, Lalith (International Coconut Community Journal, 2012)
Coconuts show a remarkable yield drop due to long dry periods caused by global climatic changes. Thus, breeding for drought tolerance has become a priority in coconut breeding in Sri Lanka. Five coconut varieties indigenous to Sri Lanka, namely Ran thembili, Gon thembili, Porapol, Bodiri and Red dwarf were screened for their drought tolerance potential in vitro. Mature zygotic embryos collected from self pollinated nuts of each variety were germinated and developed into plants with one photosynthetic leaf in Y3 medium. Water stress condition was induced by application of Polyethylene Glycol (PEG) into the culture medium. The level of PEG in culture medium was gradually increased from 2% to 7% until the plants showed water stress symptoms in leaves; yellowing and necrosis. More than 75% of zygotic embryos of all tested coconut varieties successfully germinated in vitro and developed into plants. Plants of all tested coconut varieties survived water stress caused by 4% to 6% PEG and the percentages of plant survival at different levels of PEG varied among different coconut varieties. Variety Ran thembili showed the highest survival rate (27%) at 6% PEG and overall best plant growth performances at 4% PEG among the five coconut varieties tested. Red dwarf showed the lowest survival rate at 4% to 6% PEG indicating its susceptibility to water stress. Among the coconut varieties tested, zygotic embryos of Ran thembili showed the highest drought tolerance potential.